SIMPLE MODIFICATION OF POSITIVE-BRANCH UNSTABLE RESONATOR FOR DIFFRACTION-LIMITED XECL LASER-BEAM - CHU, H; JHON, YM; CHOI, SS; PARK, DY (JAPAN J APPLIED PHYSICS, 1995)
A simple modification of the output coupler to a standard positive-branch confocal unstable resonator (PBUR) was proposed and the output characteristics were investigated and compared with those of the standard PBUR. We utilized a small convex mirror of 1.8 mm diameter as an output coupler in order to reduce the beam divergence and to eliminate the subsidiary spot caused by the Fresnel reflection effect in the standard PBUR. We obtained a single spot in the focal plane with a nearly diffraction-limited beam divergence of 0.09 mrad.